Tobacco Use Disorder, Depression and Cognitive Function to Insomnia In Indonesia: An Analysis of The 2014 Indonesian Family Life Survey Data - Muhammad A'inul Yaqin; Rizma Fithri (Universitas Negeri Surabaya, 2023)
The purpose of this study was to determine the relationship between tobacco use disorder, depression, cognitive function with insomnia in Indonesia: analysis of Indonesian family life survey 2014 data. This study used quantitative methods. This study uses documentation techniques as a data collection instrument, cross sectional data in 2014 which is data from the Indonesia Family Life Survey-5 (ILFS-5). The population in this study was 1965 early adults with male/female characteristics aged 18-40 years with sleep disorders and poor sleep quality. This study used the simple random sampling method as a sampling technique, so from the total population of 1965, 1642 early adults were used as samples. Data analysis of this study used multiple linear regression analysis. The conclusions in this study are: (1) smoking disorder does not have a significant relationship with insomnia in early adulthood with a value of r = -0.011 (p>0.05). (2) there is a positive and significant relationship between depression variables and insomnia with a value of r = 0.400 (p <0.05). (3) there is a negative and significant relationship between cognitive function variables with insomnia r = -0.051 (p<0.05). (4) tobacco use disorder, depression and cognitive function simultaneously or together with insomnia in early adulthood (p<0.05). This study shows the relationship between depression and cognitive function can have practical implications for the need to pay attention to activities that trigger depression and keep from unhealthy lifestyles such as smoking, consuming alcohol, and consuming excessive amounts of caffeine can affect sleep patterns. Especially for female subjects who have higher levels of depression than men. Tujuan penelitian ini a untuk mengetahui hubungan antara gangguan merokok, depresi, fungsi kognitif dengan insomnia di Indonesia: analisis data indonesia family life survey 2014. Penelitian ini menggunakan metode kuantitatif. Penelitian ini menggunakan teknik dokumentasi sebagai instrumen pengumpulan data, data cross sectional pada tahun 2014 yang merupakan data dari Indonesia Family Life Survey-5 (ILFS-5). Jumlah populasi dalam penelitian ini sebanyak 1965 orang dewasa awal dengan ciri-ciri laki-laki/perempuan berusia 18-40 tahun dengan gangguan tidur dan kualitas tidur yang buruk. Penelitian ini menggunakan metode simple random sampling sebagai teknik pengambilan sampel, maka dari jumlah populasi 1965 yang digunkan sebagai sampel sebanyak 1642 orang dewasa awal. Analisis data penelitian ini menggunakan analisis regresi linier berganda. Kesimpulan pada penelitian ini adalah: (1) gangguan merokok tidak memiliki hubungan yang signifikan dengan insomnia pada usia dewasa awal dengan nilai r = -0.011 (p>0.05). (2) terdapat hubungan yang positif dan signifikan antara variabel depresi dengan insomnia dengan nilai r = 0.400 (p<0.05). (3) terdapat hubungan negatif dan signifikan antara variabel fungsi kognitif dengan insomnia r = -0.051 (p<0.05). (4) gangguan merokok, depresi dan fungsi kognitif secara simultan atau bersama-sama dengan insomnia pada dewasa awal (p<0.05). Penelitian ini menunjukkan hubungan antara depresi dan fungsi kognitif dapat memiliki implikasi praktis mperlu diperhatikan aktivitas-aktivitas yang memicu depresi dan menjaga dari pola hidup yang tidak sehat seperti merokok, mengonsumsi alkohol, dan mengonsumsi kafein dalam jumlah yang berlebihan dapat memengaruhi pola tidur. Terutama bagi subjek perempuan yang memiliki tingkat depresi lebih tinggi daripada laki-laki.